Upwelling event characteristics of chlorophyll-a concentration in the surface layer of Sabah waters - Chang, Jackson ,Hian Wui; Francis, A. S.; Jedol Dayou; Justin Sentian; Chee, Fuei Pien (2018)
Using satellite-based remote sensing data, the study analysed Chl-a levels throughout Sabah’s coastal waters and correlated the Chl-a levels with the corresponding SST levels for that time and region. It was found that upwelling in Sabah coastal waters was most strongly noted in Labuan during the Northeast Monsoon (NEM), which brings strong northeasterly winds to Sabah’s west and north coast. The strong winds can be cited as the main source of increased upwelling as SST levels did not sufficiently change to suggest a strong relationship between SST and Chl-a levels.